Feasibility of The E-booklet Teaching Material Supplement on Fruit Fly (Bactrocera spp.) for High School Students on Biodiversity - Adinda Berliana Putri; Yustinus Ulung Anggraito (Universitas Negeri Semarang, 2025)
This study aims to analyze the feasibility of fruit fly e-booklets (Bactrocera spp.) for grade X SMA students on biodiversity material. This study analyzes the validity, readability test, and response of e-booklets. The method used is Research & Development (R&D) with the development model used is ADDIE with three stages, namely analysis, design, and development. The feasibility of the e-booklet media used is determined based on validation from material experts and media experts. The response to the e-booklet is determined based on teacher and student responses. The readability test using the gap test was carried out in grade X. The results of the material validation got a percentage of 91.2% with a very valid category, media validation got a percentage of 91.6% with a very valid category, the readability test got a percentage of 98.7% with an independent level category, teacher responses got a percentage of 90%, and student responses got a percentage of 82% with a very good category. Based on the results of the study, it was concluded that the e-booklet media was very valid to use, positive responses were very good from teachers and students, and readability included an independent level or free which means easy to read.